Lone male loser? Effects of spatial isolation on male pairing success in the Ortolan Bunting (Emberiza hortulana) - Steifetten, Øyvind; Starholm, Trude; Dale, Svein (Ornis Norvegica, 2023)
Cover photo: Male Ortolan Bunting. Photo: Frode Falkenberg. In small, isolated or fragmented bird populations, past studies have shown that there can be a high proportion of unpaired males. Low male pairing success is suggested to be the result of female-biased natal dispersal and low female recruitment. Indirect evidence indicates that such an effect operates among populations with different degrees of isolation, but little is known of how isolation affects male pairing success within populations. The Norwegian population of Ortolan Buntings (Emberiza hortulana) is distributed in about 50 discrete patches in an area of nearly 500 km2. In this study, we examined whether patch isolation and individual male isolation affected male pairing success. The population has a strongly male-biased sex ratio, with almost half of all males being unpaired. We found that male pairing successs was negatively related to isolation of patches and isolation of individual males in most analyses, and with significant effects in particular in some analyses of individual isolation. Patch population size was measured as the total number of males observed in a particular patch in a specific year and did not have an effect on male pairing success, and was not related to patch isolation. Even though some tests were statistically significant, the magnitude of effects were small and there was large variance in male pairing success. Variance in success suggests that other factors than isolation such as male age or experience may be just as important for male fitness within our study population. Furthermore, we suggest that small effects of isolation were due to the ability of Ortolan Buntings to move large distances within the breeding season, and that isolation effects on small spatial scales are more likely for species with restricted dispersal, such as resident species or species with high population density.